1993
DOI: 10.1159/000236497
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Complement-Derived Chemotactic Factors in Lung Injury Induced by Preformed Immune Complexes

Abstract: Our previous studies have suggested a role for complement fragments presumably activated by immune complexes in patients with hypersensitivity pneumonitis. The present study has shown that circulating complement depletion by cobra venom factor resulted in the reduction in severity of immune-complex-mediated pulmonary inflammation. The activity of chemotactic factors for neutrophils generated in bronchoalveolar lavage fluids in complement-depleted animals was significantly diminished to 61.2% compared to the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…It is well established that certain complement factors promote chemotaxis of neutrophils towards the site of inflammation. In accordance with our study, CVF treatment was reported to reduce accumulation of neutrophils in the site of lung injury [35]. The delayed onset of leucocytosis consistent with a chemotactic role of complement in normal animals was likewise observed in decomplemented rabbits in the model of pneumococcal meningitis [36].…”
Section: Discussionsupporting
confidence: 89%
“…It is well established that certain complement factors promote chemotaxis of neutrophils towards the site of inflammation. In accordance with our study, CVF treatment was reported to reduce accumulation of neutrophils in the site of lung injury [35]. The delayed onset of leucocytosis consistent with a chemotactic role of complement in normal animals was likewise observed in decomplemented rabbits in the model of pneumococcal meningitis [36].…”
Section: Discussionsupporting
confidence: 89%
“…When no granulomas are formed, more antigen might escape the lung and be available for formation of circulating immune complexes. Previous studies have suggested that immune complexes increase lung permeability (32).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies we have suggested that CD11b + leucocyte infiltration is a result of complement activation [5,8]. The anaphylatoxins C3a and C5a, released upon activation, are known to be major mediators for neutrophilic granulocyte migration [28]. In a follow‐up study in which melagatran, a direct thrombin inhibitor, was used to inhibit the IBMIR, both coagulation and complement were abrogated.…”
Section: Discussionmentioning
confidence: 99%